Алгоритм мурашиної колонії для вирішення транспортних задач із виходом з локальних мінімумів - Ясько, О. С. (ХНУРЕ, 2023)
This work is devoted to introducing to the Traveling Salesman Problem (TSP) using Ant colony algorithm. This work aims to provide an introduction to the TSP and the ant colony algorithm, and to present a detailed description of how the algorithm can be applied to solve the TSP. The work covers the basic concepts and principles of the ant colony algorithm, including pheromone trails, local search, and global search. It also includes a step-by-step guide on how to implement the algorithm. Finally, the work concludes with a discussion of the limitations and future directions of the research in this area.